Geochemical characteristics of recent 2 ka mud on the inner shelf of the East China Sea - Xiao, S. B.; Li, A. C.; Jiang, F.; Xu, F. J.; Zheng, F.; Chen, Z. (GEOCHIMICA, 2005)
The particle size of DD2 in the northern part of the muddy area along the continental margin of the East China Sea was analyzed. AMS 14 C age test and the main elements, trace elements The relationship between the content of each element and the particle size was discussed and analyzed. The relationship between them was discussed by R factor analysis. Studies have shown that nearly 2 ka to DD2 The majority of the main elements and trace elements in the pores are stable; the content of most of the elements with the grain size becomes increasing, while the content of Sr and SiO 2 The decreasing tendency of CaO, Na 2 O, Hf, Zr and Ti is poor in particle size. The results of factor analysis show that the chemical composition of DD2 pore can be It is divided into four kinds of combination types: the main characteristics of the distribution of elements in sediments are reflected, and the samples are not treated by salt beforehand to cause the combination of main elements and trace elements The Zr, Hf and Nb elements are enriched in the specific particle size components (silt), and the addition of calcareous biological components and the redistribution of elements during early diagenesis Wait. The results show that Rb, Cu, Ni, V, P, Sc, Fe 2 O 3 , Cr, K 2 O, Nb, Co, Th, Ti and Al 2 O 3 are relatively inactive elements in DD 2 pores, They can be compared with the modern Yangtze River, the Yellow River sediments, for genetic analysis. The Ti J Zr and Cr J Th ratios indicate that the pore deposits are mainly derived from the granitic Source area.
id: 570
Keywords: East China Sea continental shelf; factor analysis; geochemical characteristics; particle size

Provenance analysis of mud along the Min-zhe coast since 2 ka BP - Xiao, S. B.; Li, A. C.; Jiang, F. (Acta Sedimentologica Sinica, 2005)
id: 567